KEMERDEKAAN PERS DALAM PEMBERITAAN DI TINAJU MENURUT UNDANG-UNDANG NOMOR 40 TAHUN 1999 - Jusman Lating Grasia (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT The press has an important role in people's lives. Because the Press disseminates information, news, ideas, thoughts or feelings to a person or group of people to others. The influence of the Press itself produces a positive and negative impact therefore the press has a social responsibility for what is delivered.The research technique that I use is the Normative Juridical Research. This research is conducted by reading, quoting and making important notes that have relevance to the writing of this thesis. Juridical legal research means research that refers to the existing literature study or to the secondary data used. While Normative means legal research aimed at acquiring Normative knowledge about the relationship between one rule with other rules and application in practice.The conclusion that, first in the Act No. 40 of 1999 on the Press has been running in accordance with applicable provisions. But in its application is still found irresponsible elements. Secondly, the legal consequences arising out of the Press that are not conducive to Law No. 40/1999 are contained in Article 137, Article 154, Article 155 of the Indonesian Criminal Code which sufficiently provides a deterrent effect against persons who misuse their profession as informers Keywords: Press, Information, News